Who to believe - Hill, Edwin, 1970- (Kensington Publishing Corp., 2024)
"When popular restaurateur Laurel Thibodeau is found brutally murdered in her own home, and her husband is the prime suspect, six friends gather together, sharing theories about Laurel's death, soon realizing they each have something to hide as jealousy, revenge, adultery and greed converge"--